Bad Boy of Gospel Music : The Calvin Newton Story - Cheatham, Russ (Book collections on Project MUSE., 2003)
Biography -- Music--> ""I messed up, "" Calvin Newton lamented, after wasting thirty years and doing time in both state and federal prisons for theft, counterfeiting, and drug violations. ""These were years of my life that I could have been singing gospel music."" During his prime, he was super-handsome, athletic, and charged with sexual charisma that attracted women to him like flies to honey. Atop this abundance was his astounding voice, ""the voice of an angel."" This book is his prodigal-son story. Audacious, Newton never turned down a dare, even if it meant climbing on the roof of a speedi